The effect of discovery learning on chest pass learning outcomes in basketball games - Puguh Satya Hasmara; Basuki Basuki; Ilmul Ma'arif; Guntum Budi Prasetyo (Sriwijaya Journal of Sport, 2024)
Background Problems: In learning chest pass students at school need an effective and appropriate learning method required at the time of learning the discovery learning method is one option that can be used by teachers, using this approach the teacher must create something new by creating different learning conditions and learning activities by the demands and development of education. Research Objectives: This study aimed to determine the effect of the Discovery Learning model on Chest Pass on Basketball Games. Methods: Quasi-experimental research, the population of this study was VII grade students of SMPN 2 Gondang with a total of 112 students, sampling with a Random Sampling technique so that it was known that the VII A class sample was 65 students. Instruments include a chest pass process assessment test and a skill test bouncing the ball against the wall, a descriptive test data analysis technique, and a t-test with the help of the SPSS computer program. Results: The results of this study were obtained from the results of this study in the paired sample-test table in the calculation of the results test and process test obtained a Sig (2-tailed) value of 0.000. For that 0.000<0.05, then H0 is rejected, and Ha is accepted. Conclusion: the conclusion is that there is an effect of the Discovery learning model on chest passes in basketball games.